The malling of the movies: Film exhibition reforms, multiplexes, and film consumption in the new millennium in urban China. Issue 3 (1st September 2016) - Lu, Yi
ABSTRACT: The aim of this article is to examine China's multiplex boom in the new millennium. As a result of film exhibition deregulation policy, the hot investment trend caused a 'cinema building frenzy', which significantly changed the face of the movie exhibition sector in the Chinese film industry. The dramatic growth in the multiplex is congruent with commercial real estate developments, urbanization and consumerism in China. This article considers the multiplex as a cinematic heterotopia and the state's support for the multiplex development as a case study of China's strategies of 'controlled commodification'. I argue that through the modernization and commodification of cinema-going space, the state recreated the social relations between the government and the film industry, as well as between cultural regulation, people's public life and human behavior.